BPAs probability-based clearance buffers. II. Application to the design of new lines. - Reding, J.L (IEEE Transactions on power delivery)
A procedure to develop clearance buffers for the design of a new line, based on probabilistic techniques, as used by the Bonneville Power Administration (BPA) is described. A statistical clearance model for new lines (the line design nominal statistical clearance model) tailors the expected scatter in field clearance about a design clearance for a new line. This expected clearance scatter results from measurement tolerances in the design and construction of an overhead line. The paper discusses the use of assurance levels for maintaining regulatory clearance requirements in the field and relates those assurance levels to the statistical clearance model. Using the statistical clearance model and assigned assurance levels, statistical clearance buffers are developed for various crossing types typically used in the design of new lines at BPA. Finally, a short discussion concerning the development of probabilistic clearance buffers for other activities not included in the standard set of crossing types is included.